Expert Review: Prevention of Obstetrical Venous Thromboembolism. Issue 2 (24th June 2022) - Friedman, A.; D'Alton, M.
Abstract : ( Am J Obstet Gynecol . 2021;225:228–236) Approximately 9% to 10% of maternal deaths are related to thrombotic pulmonary embolism. The American College of Obstetricians and Gynecologists (ACOG), the Royal College of Obstetricians and Gynaecologists (RCOG), the American College of Chest Physicians (ACCP), the American Society of Hematology, the National Partnership for Maternal Safety, and the Society for Maternal-Fetal Medicine have all published dissimilar recommendations for obstetrical venous thromboembolism (VTE) prophylaxis. Several additional studies have concluded mechanical prophylaxis alone was ineffective during childbirth and during recovery and sequential compression devices were only in use 17% to 21% of the time. While the use of mechanical prophylaxis has become more common, the mortality rate for VTE has not decreased. The United Kingdom implemented guidelines in 2004 for low–molecular-weight heparin prophylaxis and has shown a 40% reduction in maternal deaths from VTE. However, cost, lack of evidence, and safety concerns are included in the argument against heparin prophylaxis. This review focuses on guidelines for heparin prophylaxis during antepartum hospitalizations and following cesarean deliveries (CD).